2002
DOI: 10.5980/jpnjurol1989.93.681
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Surgical Invasiveness of Augmentation Ileocystoplasty Applying the Systemic Inflammatory Response Syndrome Score in Patients With Spina Bifida

Abstract: When evaluated by the SIRS score, the factors related to the surgical invasiveness of augmentation ileocystoplasty were a longer operating time and concurrent shunt diversion. The higher invasiveness of this operation compared with major urological operations was also revealed. These facts should be considered carefully when the indications for augmentation ileocystoplasty are determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…SIRS has recently been used in several studies to estimate the magnitude of surgical invasiveness in the peri-and postoperative periods [9,12]. Haga et al [5] indicated that SIRS is a useful parameter for early detection of postoperative complications and end-organ dysfunction after gastrointestinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…SIRS has recently been used in several studies to estimate the magnitude of surgical invasiveness in the peri-and postoperative periods [9,12]. Haga et al [5] indicated that SIRS is a useful parameter for early detection of postoperative complications and end-organ dysfunction after gastrointestinal surgery.…”
Section: Discussionmentioning
confidence: 99%